An Analysis of The Level of Polite Utterances in Sasak Language: A Case Study in Central Lombok - Nurullayali, Baiq; Sartika, Sartika; Supriadin, Supriadin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
This research aims to identify the way of polite language used by Sasak people in Central Lombok. In this research, qualitative descriptive method was employed in analyzing the data. There were three participants that consist of Sasak native speaker from two villages such as Beraim and Dakung village. The data were collected through three techniques that are, observation, interview and documentation. The Results of this research showed that firstly, Sasak language has three levels of polite utterances used by Sasak people such as most polite (Base Alus Utami), more polite (Base Alus Madya), and polite (Base Sasak Biase). When kingdom was exist, Base Alus Utami only used by Perwangse, who was the king or people with high class level in Lombok Island and marked by Raden/Datu, and Dende at the first name. But, when they interacted with the lower class, they used biase language while the lower class of people must use Base Utami then, Base Alus Madya only used by people with the second level in society Baiq and Lalu at the first name, and Base Sasak Biase used by people with the lower class, called Jajar Karang. Secondly, the next generation in Sasak today do not really cosidere the rules when they using the polite language as people used in the past. It can be seen when they are communicating each other. They cannot able to speak with Base Alus Utami even speak with the older people. Only some of old people are still maintenance this language and teach their children but it is so rarely.